Renal Doppler sonography as a non-invasive technique for early detection of reno-vascular changes in sickle cell disease in children - Mona Hassan Eltagui; Hadeel M. Seif Eldein; Marwa Abd Elhady; Dalia El-Sayed; Nouran Momen; Yasmeen M. M. Selim; Mai Mohammed Abd EL Salam (SpringerOpen, 2023)
Abstract Objective Early identification of sickle renovascular changes via renal Doppler sonography among sickle cell disease patients to help in early diagnosis and interventions to prevent progression to end-stage renal disease. Methods Forty-five SCD children were included along with 45 healthy control children. Renal Doppler sonography (PI and RI) was performed on all subjects. Laboratory investigations were done: Hb electrophoresis, complete blood picture with blood indices, reticulocyte count, liver enzymes (ALT and AST), HCV serology, serum ferritin, and lactate dehydrogenase (LDH). Urine analysis and albumin/creatinine ratio in urine were done for all patients as well. Results The study group consisted of 45 SCD patients, 27 (60%) males with a mean age of 12 years (± 3 years). By performing renal Doppler sonography, it was found that all study groups had significantly higher Doppler indices (resistivity index and pulsatility index) compared to the control group. Results of renal Doppler sonography revealed that the main renal pulsatility index was positively correlated with the main renal resistance index (r = 0.454, p = 0.002). Conclusion Doppler indices (resistance index and pulsatility index) were of value to assess reno-vascular changes in SCD, Thus, renal Doppler indices could be an early technique in the assessment of sickle renovascular changes, so treatment can be started at an early stage before progressive affection of renal function.